MS-Math Feedback 2017 (2016)
The MS Mathematics enrolled 51 new students from Fall 2011 to Fall 2016, and averages 30 continuing students in the program. A total of 40 degrees have been awarded since Fall 2011. Over the years, we have discussed strategies for increasing enrollment, but the application numbers seem to have plateaued. The University should consider whether or not the MS Mathematics program is well suited as a special session (self-supporting) degree. Given the role that the MS Mathematics plays in providing Mathematics instructors for the University, a move of the program to stateside might be appropriate. If the program is kept in Extended University, the alternative would be to try raising student fees and hope that the impact on student enrollment isn't too extremely negative. It is feared that a reduction in marketing costs would negatively impact enrollment more than a fee increase.